Intellectual property and the ethical/legal status of human DNA: The (ir)relevance of context - Pullman, Daryl; Nicholas, George (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2011)
There has been much discussion in recent years about the ethical and legal status of human DNA. This topic is of great relevance and importance to Aboriginal communities because the question of who has the right of access to and control over the DNA of individual persons, or of DNA extracted from human remains, could have implications for an entire community. In another context an individual’s decision to contribute a blood sample for health research could reveal much about the health status of other members of the community. Who has the right to control access to DNA or a community’s narrative of its origins? While some have argued that human DNA should be considered cultural property in order to ensure appropriate control of genetic information, we question the wisdom of this approach. Although we acknowledge that the differing contexts in which DNA is extracted and utilised could require unique approaches in some circumstances, we argue that emphasis should be primarily on the nature of the relationships established and maintained between researchers and descendant communities and only secondarily on the unique status of the DNA itself.